Amendment of Calculation Method Airborne Soundproofing of Light Multi-Layer Enclose Structures of Residential Buildings - Jasur Gayratugli Rashidov (International Journal of Community Service & Engagement, 2021)
This research paper describes airborne soundproofing of multilayer light enclose structures at the stage of designing and reconstruction of residential buildings, with the help of which it is possible to obtain a sufficiently reliable calculation, representing the correct passage and radiation of the sound stream in these structures, taking into account the finiteness of the dimensions, fixing conditions, physical and mechanical characteristics of materials and the method of proper installation.